Evaluation of Land Cover Based on The Aceh Province Spatial Plan in The Krueng Aceh River Basin - Ichsan Ichsan; Hairul Basri; Muhammad Rusdi (Department of Agricultural Engineering, Syiah Kuala University, 2022)
Abstract. This study aims to analyze the area and distribution of land cover in the last 10 years in the Krueng Aceh and evaluate the alignment between the regional spatial plan (RTRW) and the land cover in the Krueng Aceh watershed. The results of the analysis were obtained through digital image processing derived from Landsat 7 ETM 2009 and Landsat 8 OLI 2020. This study shows that land cover in the form of primary forest has changed from 2009 to 2020, wherein 2009 primary forest cover had an area of 60,245.62 ha or 34.11% of the entire area while in 2020 it was reduced to 48,512.00 ha or 27.47% of the entire area. And Based on the results of the evaluation of the consistency of land closure conditions in the Krueng Aceh watershed against the Aceh Provincial RTRW, 98.40% of the area of the Krueng Aceh watershed obtained land cover consistent with the RTRW. But Based on the results of the Evaluation of the Consistency of Area Status in the Krueng Aceh River Basin against the Aceh Province RTRW, it was found that an area of 176,301.71 ha or equal to 99.99 % of the area of the Krueng Aceh River Basin, the status of the Area was consistent with the RTRW.